2004
DOI: 10.1017/s0967199404002928
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cryodevice type and donors' sexual maturity on vitrification of minke whale (Balaenoptera bonaerensis) oocytes at germinal vesicle stage

Abstract: SummaryGerminal-vesicle-stage oocytes enclosed with compact cumulus cell layers (COCs) were recovered from adult or prepubertal minke whale ovaries, and were vitrified in a solution containing 15% ethylene glycol, 15% DMSO and 0.5 M sucrose using either a Cryotop or an open-pulled straw (OPS) as the cryodevice. The post-warm COCs with normal morphology were cultured for 40 h in a 390 mosmol in vitro maturation medium, and oocytes extruding the first polar body were considered to be matured. The proportion of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 24 publications
1
35
0
Order By: Relevance
“…Therefore, it seems that 40 h is an appropriate IVM duration for common minke whale oocytes, which is similar to that for the Antarctic minke whale oocytes [6]. Regarding sexual maturity of the oocyte donor, the present results show that oocytes from the adult whales tended to produce a higher IVM rate than those from the prepubertal whales; this is consistent with our previous studies [5,6]. Fujihira et al [6] reported that the IVM rates (60.9 and 53.1%) of fresh immature oocytes collected from adult and prepubertal Antarctic minke whales were not significantly different, but that the parthenogenetic activation rate of oocytes from adult whales (76.7%) was significantly higher (P<0.05) than that of oocytes from prepubertal whales (46.4%).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Therefore, it seems that 40 h is an appropriate IVM duration for common minke whale oocytes, which is similar to that for the Antarctic minke whale oocytes [6]. Regarding sexual maturity of the oocyte donor, the present results show that oocytes from the adult whales tended to produce a higher IVM rate than those from the prepubertal whales; this is consistent with our previous studies [5,6]. Fujihira et al [6] reported that the IVM rates (60.9 and 53.1%) of fresh immature oocytes collected from adult and prepubertal Antarctic minke whales were not significantly different, but that the parthenogenetic activation rate of oocytes from adult whales (76.7%) was significantly higher (P<0.05) than that of oocytes from prepubertal whales (46.4%).…”
Section: Discussionsupporting
confidence: 91%
“…In those studies, 15-20% fetal whale serum was incorporated into the IVM media with osmolarity of approximately 310 mOsm, but the IVM media was not supplemented with whale follicular fluid (wFF). Iwayama et al [4,5] added 10% or 50% wFF to IVM media for fresh or vitrified Antarctic minke whale oocytes and found that the duration of IVM culture could be shortened to 30-40 h. The osmolarity of wFF (387.9 ± 3.1 mOsm; n= 23 [4]) is higher than those of bovine and porcine FF (approximately 300 mOsm). Addition of 10% wFF to IVM medium and adjustment of the osmolarity t o 3 9 0 m O s m p r o v i d e s a b e t t e r a n d m o r e physiological environment for in vitro maturation of common minke whale oocytes, although the osmolarity of wFF in common minke whales has not been examined [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, the study of such reproductive technologies in marine mammals has been delayed because of limited availability of their gametes. To ameliorate this situation, we have participated in the Japanese Whale Research Program with Special Permit in the Antarctic and tackled the cryopreservation of gametes, in vitro maturation of oocytes, and in vitro fertilization and in vitro production of embryos in minke whales (Fukui et al, 1997a, b;Mogoe et al, 1998;Asada et al, 2000Asada et al, , 2001aIwayama et al, 2004). Although spermatozoa could penetrate into 55-63% of oocytes following in vitro insemination, a considerable number of penetrated sperm nuclei failed to transform into male pronuclei, and none of the fertilized ova developed to blastocysts (Fukui et al, 1997b;Asada et al, 2001a).…”
Section: Introductionmentioning
confidence: 99%